PENGARUH WORK LIFE BALANCE DAN SELF-EFFICACY TERHADAP EMPLOYEE ENGAGEMENT PADA CV GUNA ABADI - Nugrahaningsih, Tri Hardjanti; -, Vivian Marcelina (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aimed to analyze the extent to which Work-Life Balance and Self-Efficacy contribute to Employee Engagement at CV Guna Abadi. Involving 100 employees from the company, this study meticulously employed methods to test the reliability and convergent validity of all investigated variables. The analysis results indicate that all variables exhibit good reliability, signifying consistent and accurate measurement. Furthermore, convergent validity was confirmed, demonstrating that the indicators used are valid and the research model is reliable. Further analysis revealed that both work-life balance and self-efficacy significantly contribute to employee engagement. These findings offer valuable insights for CV Guna Abadi's management in enhancing employee engagement. However, as this study was limited to a single company entity, subsequent research is recommended to broaden the scope of subjects for wider generalization of the results.